Liver disease and malnutrition - YILMAZ, YUSUF (ELSEVIER SCI LTD, 2013)
Patients with hepatic disorders are exceptionally vulnerable to developing malnutrition because of the key role played by the liver in regulating the nutritional state and the energy balance. Moreover, the presence of chronic liver disorders could reduce the appetite and thus influence the nutrient intake. Poor nutritional status has been shown in various patient groups with hepatic disorders, and particularly in patients with alcoholic cirrhosis who are at high nutritional risk. It is well established that malnourished patients with liver diseases generally have a higher risk of developing adverse clinical outcomes and increased healthcare costs. Nutrition screening with the Subjective Global Assessment and anthropometric measurements are an important first step in the early identification of malnutrition and initiates the whole nutrition care process. It is therefore important for appropriate nutrition policies and protocols to be implemented so that all patients with chronic liver diseases are monitored closely from a nutritional standpoint. Early and evidence-based nutritional interventions are eagerly needed to minimize the nutritional decline associated with chronic liver disorders and ultimately improve the prognosis of such patients. This review includes a comprehensive analysis of methods to identify malnutrition in patients with chronic liver diseases as well as the extent and impact of the malnutrition problem in selected patient populations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Nutrition; Liver; Cirrhosis; Subjective global assessment; Anthropometry; Clinical outcomes; NONALCOHOLIC FATTY LIVER; SUBJECTIVE GLOBAL ASSESSMENT; GLYCATION END-PRODUCTS; VITAMIN-A-DEFICIENCY; HEPATITIS-C; NUTRITIONAL-STATUS; ENTERAL-NUTRITION; ALTERED EXPRESSION; CIRRHOTIC-PATIENTS; LOW-CARBOHYDRATE